Investigating the antioxidant and preventing DNA-damage properties of various honeys in Phitsanulok province - Laywisadkul, Srisangwan; Weerawatanakorn, Monthana; Maneerattanarungrojn, Chaichan; Sujipuli, Kawee (Food and Applied Bioscience Journal, 2017)
A honey has been well known as nutritional food products since it rich in nutrients and bioactive compound such as phenolic compounds possessing antioxidant activity. Many literatures have been reported that the difference sources of honey cause the significant differences in their antioxidant contents and their protective effects against DNA damage. Therefore, the aim of the present study was to evaluate bioactive components, antioxidant properties, and DNA damage protection of honey from different honey brands sold in the markets in Phitsanulok province, Thailand. The results revealed that eleven commercial honey products available in the markets were difference in physicochemical properties such as moisture, pH, ash, and sugar contents. Three out of tested eleven honey products had high amount of phenolic compounds, contributed to their antioxidant activities by DPPH assay and the mechanism is proven to be through free radical scavenging activities rather than ion-chelating activity by the protective DNA damage. These indicated that honey contains natural antioxidants and it could be used as an important ingredient of the functional food in particular functional beverage.